(untitled) (Bangladesh Journal of Plant Taxonomy, 2008)
The family Liliaceae A.L. de Jussieu has been revised for Bangladesh and a total of 34 species with one variant under 16 genera have been recorded. Artificial dichotomous keys to the genera and species have been given. Descriptions have been provided for each taxon, and local names, flowering and fruiting periods have been added wherever available. Out of 34 species, 16 species are native/naturalized and 18 species, including 1 variant, are exotic. Four genera, ten species and one variant have been documented for the first time in Bangladesh. Keywords: Liliaceae, Systematic studies, Bangladesh Â DOI: 10.3329/bjpt.v15i2.1741 Â Bangladesh J. Plant Taxon. 15(2): 115-128, 2008 (December)